SAAT ANAK SD BELAJAR JADI WARGA NEGARA DENGAN REFLEKSI EDUKASI KEWARGANEGARAAN MASA KINI - Dicky Chandra Nababan; Galuh Arumsari; Naila Khairunisa; Natasya Permata Putri; Yulia Elfrida Yanty Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Citizenship education for elementary school students plays a crucial role in shaping responsible and participatory citizens. This study reflects on the current practices and challenges of implementing civic education in Indonesian elementary schools, particularly in the context of social changes and the digital era. Using a qualitative descriptive approach, data were collected through literature analysis, classroom observations, and teacher interviews. The findings indicate that while civic education is integrated into the curriculum, its delivery often focuses on rote learning rather than fostering critical thinking and participatory skills. Teachers face challenges in contextualizing citizenship concepts in ways that are engaging and relevant to students’ everyday lives. The study suggests the need for experiential and project-based approaches to help students internalize civic values. These findings have implications for teacher professional development, curriculum reform, and the broader discourse on democratic education in Indonesia